Компаративна дозиметриска евалуација на референтните вредности при дводимензионално и тридимензионално планирање на интракавитарна брахитерапија со висока брзина на доза кај локално напреднат карцином на цервикс - Клисаровска, Виолета (Медицински факултет, УКИМ, Скопје, 2018)
Introduction: Intracavitary brachytherapy (ICBT) is one of the most effective radiotherapy techniques in the treatment of cervical cancer, which complements the radiotherapy dose performed with percutaneous radiotherapy. In conventional two-dimensional (2D) treatment planning, the dose is prescribed at reference points. Three-dimensional planning (3D) is in volume structures, which allows radiation with precise and controlled high dose in the tumor, with maximum protection of organs at risk. Material and methods: The study analyzed data from a total of 200 patients all with locally advanced inoperable cervical cancer, treated in the University clinic for radiotherapy and oncology. 100 of these were the examined group (EG), in which prospectively dosimetrically we analyzed 300 brachytherapy applications conducted according to 3D - planning and compared with virtual 2D - planning. Retrospectively we analyzed the frequency of appearance of radiation-induced acute side effects of organs at risk (bladder and rectum) in the control group (CG) consisting of 100 patients (300 brachytherapy applications), treated in the University clinic for radiotherapy and oncology. In CG brachytherapy was conducted according to the 2D method of planning. Concurrent chemotherapy with external radiotherapy was performed in all patients, with subsequent ICBT with high dose rate. 2D - planning was carried out on radiography obtained with C-arm or a classic SIMULIX simulator, at ICRU reference points, and 3D - planning of a precise CT - shaped volume of interest. In 2D - plans, the dosage was calculated and reported according to the recommendations of the International Commission for Radiation Units and Measurements ICRU 38, and in 3D - plans adapted according to the „ICRU 89 Minimum Standards“. ICBT was conducted with Gamma Med apparatus, with radioactive source Iridium 192. Results: Regarding the target volume, the comparison in the EG showed significantly higher average values in relation to the ICRU reference point „A“ (left 7,15 Gy, right 7,17 Gy) responsible for the target volume in 2D - planning, compared with its reconstruction in 3D - planning (left 6,94 Gy, right 7,02 Gy). 3D - planning through the dose-volume histogram demonstrated the isoxic coverage of the target volume in its entirety, and not just in the dot. It was found that an average value of 53,74% of the target volume received 100% and an average value of 58,75% receiving 90% of the given dose. That is, in 100% of the target volume an average dose of 1,76 Gy was achieved, in 95% 2,79 Gy and in 90% 3,24 Gy. Regarding the risk organs, in the EG, with 2D - planning, significantly lower dose values were verified compared to 3D - planning. In the bladder 2D analysis showed an average dose of only 3,45 Gy at the ICRU reference point, but 3D planning showed significantly higher average doses, as follows: a maximum dose of 7,97 Gy, a dose of 4,68 Gy in 2 ccm of total volume and a dose of 4,14 Gy in 2 ccm volume from the wall of the bladder. In rectal 2D - planning, an average dose of 2,91 Gy at the ICRU reference points, and significantly higher average dose values were obtained in 3D - planning, as follows: 5,77 Gy as the maximum dose and 3,79 Gy in 2 ccm of total volume and a dose of 3,59 Gy in 2 ccm volume from the wall of the rectum. Patients with EG and CG differed significantly in relation to the extent of acute toxicity of adverse effects that were manifested in the form of radiation bladder cystitis (p <0.001) and radiative proctitis on the rectum (p = 0.0038). In IG, the side effects of the bladder and rectum were significantly lower in degree of toxicity compared to KG. Conclusion: CT based 3D - planning customizes the treatment through volume presentation, resulting in a real and accurate identification of the dose in the target volume, but the greatest benefit is in the dosage control of the organs of risk.
Докторска дисертација одбранета во 2018 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Климе Ѓорески.
Keywords: high-dose-rate brachytherapy, cervical carcinoma, intracavitary brachytherapy, organs at risk